Evaluating the Justice Framework in Land Acquisition: Legal and Policy Review of Government Regulation No. 39/2023 in Indonesia - Damianus Krismantoro (Khazanah Hukum, 2025)
Land acquisition for public interest is a strategic instrument in Indonesia’s national development agenda, yet it continues to generate legal, social, and human rights controversies. Previous studies tend to focus on procedural or administrative aspects, often overlooking normative justice, institutional coherence, and comparative legal perspectives. This study seeks to fill that gap by critically analyzing Government Regulation No. 39 of 2023 as a revision of Government Regulation No. 19 of 2021, focusing on its consistency with the principles of justice, the constitutional hierarchy of laws, and the broader goals of agrarian reform. Using a qualitative-descriptive method based on normative legal research, this article examines key legal instruments such as Law No. 2 of 2012, the Job Creation Law (Law No. 6 of 2023), and the Basic Agrarian Law (Law No. 5 of 1960). It integrates normative, institutional, and comparative frameworks to evaluate the role of the Land Bank Institution, the transparency of compensation mechanisms, and the degree of public participation. The article also assesses whether Government Regulation 39/2023 aligns with the redistributive spirit of agrarian reform and safeguards against potential human rights violations. Findings suggest that while the regulation introduces improvements in procedural structure and institutional roles, it remains limited in addressing structural injustices, particularly in relation to forced displacement, customary land claims, and access to legal remedies. This article offers a novel contribution by bridging doctrinal analysis with critical human rights perspectives and international comparisons, emphasizing the need for a justice-oriented reform in land acquisition policy.